Traumatic Dissection of Four Brain-Supplying Arteries without Neurologic Deficit. (August 2014) - Pröscholdt, Florian; Heining, Sandro; Powerski, Maciej; Nolte, Christian H.; Ertel, Wolfgang
Study Design: Case report and review of the literature. Objectives: Case report of a traumatic dissection of all major brain-supplying arteries resulting from a horseback-riding accident. Overview of the literature on diagnostic and therapeutic recommendations. Methods: Case presentation. For the discussion, handpicked articles and PubMed database research with the keywords "dissection, " "vertebral artery, " "spine trauma, " "computed tomography, " "magnetic resonance imaging, " and "angiography" were used. Results: Despite high-energy induced acute lesion of all four cervical arteries, this 45-year-old patient did not demonstrate signs of microemboli nor suffer from stroke. Conclusion: In case of high-energy trauma of the head and/or the neck, emergency physicians must consider traumatic cervical artery dissection (TCAD). Thus, emergency care algorithms should routinely include computed tomography angiography and magnetic resonance imaging. Although the incidence of TCAD-induced stroke is low, antiplatelet therapy is recommended in the presence of TCAD.